48-urno neinvazivno ambulantno merjenje krvnega tlaka pri bolnikih s končno ledvično odpovedjo, zdravljenih s pomočjo hemodialize - Zbačnik, Rok (Medicinski razgledi, 1998)
The purpose of this prospective study was to determine the potential effects of various factors on blood pressure (BP) levels in 40 patients treated by haaemodialysis. A 48-hour non-invasive ambulatory BP monitoring was used because it allows for the evaluation of BP values and its dynamics outside thehospital setting. The study showed BP was not affected by sex, age, years on dialysis, interdialytic weight gain and starting hour of the haemodialysis treatment (p > 0,05). The erythropoetin therapy resulted in higher systolic and dyastolic BPs (p = 0.03 and p = 0.008, respectively). Haemodialysis patients on antihypertensive therapy had higher systolic BPs than those recie-ving no therapy (p = 0.035), which suggested that the control of hypertension was inadequate despite the use of antihypertonic drugs. Patients treated by acetatefree dialysis method had lower diurnal nocturnal mean dyastolic BPs than those treated by a conventional bicarbona- te method (p = 0.008 and p = 0.0016, respectively). No difference in mean BPs was found between patients treated by bicarbonate, acetate and haemo(dia)filtration haemodialysis method. Systolic BPs were significantly lower during a 5-hour period on the non-dialysis day than during the dialysis session (p < 0.015). These results confirmed the influence of the stressful hospital environment onBP and indicated the inadequacy of BP values measured at the beginning of haemodyalisis for an objective evaluuation ofhypertension control. We think that an objective evaluation of BP levels in patients treated by chronic haemodyalisis for end stage renal failure a regular 48-hour non-invasive ambulatory BP monitoring should be used at least once a year.
Keywords: Kidney failure, chronic; ledvične bolezni; Therapy; hemodializa; Complications; zdravljenje; krvni tlak; Blood pressure monitoring, ambulatory; Hemodialysis; Hypertension; Diagnosis; Erythropoietin